A role for 3′-O-β-D-ribofuranosyladenosine in altering plant immunity. (January 2019) - Drenichev, Mikhail S.; Bennett, Mark; Novikov, Roman A.; Mansfield, John; Smirnoff, Nick; Grant, Murray; Mikhailov, Sergey N.
Abstract: Our understanding of how, and the extent to which, phytopathogens reconfigure host metabolic pathways to enhance virulence is remarkably limited. Here we investigate the dynamics of the natural disaccharide nucleoside, 3′-O-β-D-ribofuranosyladenosine, in leaves of Arabidopsis thaliana infected with virulent Pseudomonas syringae pv. tomato strain DC3000. 3′-O-β-D-ribofuranosyladenosine is a plant derived molecule that rapidly accumulates following delivery of P. syringae type III effectors to represent a major component of the infected leaf metabolome. We report the first synthesis of 3′-O-β-D-ribofuranosyladenosine using a method involving the condensation of a small excess of 1-O-acetyl-2, 3, 5-three-O-benzoyl-β-ribofuranose activated with tin tetrachloride with 2′, 5′-di-O-tert-butyldimethylsilyladenosine in 1, 2-dichloroethane with further removal of silyl and benzoyl protecting groups. Interestingly, application of synthetic 3′-O-β-D-ribofuranosyladenosine did not affect either bacterial multiplication or infection dynamics suggesting a major reconfiguration of metabolism during pathogenesis and a heavy metabolic burden on the infected plant. Graphical abstract: Image 1 Highlights: We describe the first synthesis of 3′-O-β-D-ribofuranosyladenosine. 3′-O-β-D-ribofuranosyladenosine is a natural disaccharide nucleoside induced by phytopathogens. 3′-O-β-D-ribofuranosyladenosine is plant derived. 3′-O-β-D-ribofuranosyladenosine accumulates less in A. thaliana hyper-resistant mutants. The amount of 3′-O-β-D-ribofuranosyladenosine can accumulate to ∼1.5 μg per infected leaf.